Investigation on Knowledge and Awareness about HIV/AIDS among First Year Medical Students in Guntur, Andhra Pradesh, India - Jogdand, Keerti S.; Yerpude, Pravin N. (Perspective of Recent Advances in Medical Research Vol. 1, 2022)
The current study was done to study the awareness and knowledge about HIV/AIDS among the first year medical students. In recent years, adolescent has become one of the high-risk groups for HIV. Meanwhile, good HIV awareness and positive attitude are essential for HIV prevention. A Cross sectional study was done among 138 first year medical students. The information was collected form them within 2-3 weeks of admission using pre-test semistructured questionnaire. All the students had heard about HIV/AIDS. Only 55.79% of them could tell all the modes of transmission correctly. 26.78% students had the misconceptions regarding the mode of spread of this disease. The commonest misconception was that HIV get transmitted through working in same environment (6.52%) followed by superficial kissing (5.79%) and sharing utensil with patient in 4.35% students. All the preventive measures were known to 77.53 % students. The single most crucial element in any nation's national AIDS prevention and control programme continues to be health promotion, which involves providing extensive information, education, and communication to change the behaviour of groups of people.